2018
DOI: 10.1002/cbin.10936
|View full text |Cite
|
Sign up to set email alerts
|

WNT5A promotes migration and invasion of human osteosarcoma cells via SRC/ERK/MMP‐14 pathway

Abstract: WNT5A, a representative ligand of activating several non-canonical WNT signal pathways, plays significant roles in oncogenesis and tumor inhibition. It has been shown that the non-receptor tyrosine kinase SRC is required for WNT5A-induced invasion of osteosarcoma cells. However, the precise molecular mechanism underlying WNT5A/SRC-mediated osteosarcoma cells invasion remains poorly defined. The study was designed to explore the role of ERK1/2 in WNT5A/SRC-induced osteosarcoma cells invasion and the downstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Here we found that DCLK1 overexpression induced the phosphorylation of ERK MAPK pathway (Figure 4(a)), but not JNK or p38 MAPK pathways, in T47D cells. Previous studies demonstrated that activation of ERK MAPK pathway can promote the expression of MT1-MMP, which is a key protease and plays an important role in pro-migration proteolysis and is thereby involved in many cancer metastases [2022]. We observed that DCLK1 overexpression caused an upregulation of MT1-MMP, which was likely due to activation of ERK MAPK pathway (Figure 4(a)).…”
Section: Resultssupporting
confidence: 55%
“…Here we found that DCLK1 overexpression induced the phosphorylation of ERK MAPK pathway (Figure 4(a)), but not JNK or p38 MAPK pathways, in T47D cells. Previous studies demonstrated that activation of ERK MAPK pathway can promote the expression of MT1-MMP, which is a key protease and plays an important role in pro-migration proteolysis and is thereby involved in many cancer metastases [2022]. We observed that DCLK1 overexpression caused an upregulation of MT1-MMP, which was likely due to activation of ERK MAPK pathway (Figure 4(a)).…”
Section: Resultssupporting
confidence: 55%
“… 65 Only one study noted increased mRNA of WNT7b in human OS cell lines, 61 while another reported that the prototypical non-canonical Wnt ligand Wnt5a promotes the migration and invasion of a human OS cell line in vitro. 66 …”
Section: Discussionmentioning
confidence: 99%
“…Integrins, MMP-2, MMP-9, MT1-MMP and other molecules are known to be involved in the migration and invasion in osteosarcoma cells. In addition, it has been reported that MMP-2, MMP-9 and MT1-MMP may be modulated via the PI3K/Akt and Erk1/2 signaling pathways [25][26][27][28]. The extracellular matrix (ECM) serves as a barrier for the metastasis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%